How to prevent the next pandemic - Gates, Bill (London : Penguin Books, 2023)
The COVID-19 pandemic isn't over, but even as governments around the world strive to put it behind us, they're also starting to talk about what happens next. How can we prevent a new pandemic from killing millions of people and devastating the global economy? Can we even hope to accomplish this? Bill Gates believes the answer is yes, and in this book he lays out clearly and convincingly what the world should have learned from COVID-19 and what all of us can do to ward off another disaster like it. Relying on the shared knowledge of the world's foremost experts and on his own experience of combating fatal diseases through the Gates Foundation, he first makes us understand the science of corona diseases. Then he helps us understand how the nations of the world, working in conjunction with one another and with the private sector, can not only ward off another COVID-like catastrophe but also go far to eliminate all respiratory diseases, including the flu. Here is a clarion call - strong, comprehensive, and of the gravest importance - from one of our greatest and most effective thinkers and activists.
Register
Slovník
Keywords: pandémie -- prevencia a kontrola; choroby infekčné; zdravie verejné; prevencia primárna; plánovanie strategické; COVID-19; práce populárne